2015
DOI: 10.1016/j.jcrs.2014.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Haigis-L formula for calculating intraocular lens power in Asian eyes after refractive surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
4
16
1
2
Order By: Relevance
“…Then, a number of regression formulas-Shammas-PL [5] which uses data available at the time of cataract surgery to predict the post refractive surgery keratometry and W-K-M [13] method which convert anterior corneal power from Atlas topographyare described in different articles. Haigis-L uses linear regression to optimize the estimate of corneal power from standard keratometry [6], which is the most popular method for IOL power calculation after refractive surgery, especially for Asian and German [25,26]. Unlike double-K method, the Shammas-PL and Haigis-L determine the ELP without the central corneal power data.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a number of regression formulas-Shammas-PL [5] which uses data available at the time of cataract surgery to predict the post refractive surgery keratometry and W-K-M [13] method which convert anterior corneal power from Atlas topographyare described in different articles. Haigis-L uses linear regression to optimize the estimate of corneal power from standard keratometry [6], which is the most popular method for IOL power calculation after refractive surgery, especially for Asian and German [25,26]. Unlike double-K method, the Shammas-PL and Haigis-L determine the ELP without the central corneal power data.…”
Section: Discussionmentioning
confidence: 99%
“…In Wong’s study, the Asian eyes with previous myopic LASIK or photorefractive keratectomy (PRK) had cataract surgeries with IOL power calculated by 4 formulas. Haigis-L formula turned out to have the highest percentage of cases that achieved the refraction of targeted SE ±0.50 D and SE ±1.00 D [ 14 ]. A meta-analysis by Chen et al also concluded that the clinical inquiry was inaccurate in predicting postoperative refraction as compared to the Haigis-L formula [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Refractive outcomes of Haigis-L formula for calculation intraocular lens power in Asian eyes with axial lengths longer than 25.0 mm that had a previous myopic laser in situ keratomileusis or photorefractive keratectomy are evaluated in (Wong et al, 2015). The predictability of being within ±0.5 D and ±1.0 D of the target was 35.7 % and 63.1 %, respectively.…”
Section: Calculation Of Intra-ocular Lens For Non-normal Eyesmentioning
confidence: 99%